Studi Pemikiran Fatima Mernissi Tentang Kesetaraan Gender - Eko Setiawan (Yinyang: Jurnal Studi Islam Gender dan Anak, 2019)
Fatima Mernissi is a figure of modern Muslim feminism. He was an Arab Muslim woman sociologist who cares about gender issues in the lives of Muslims. Gender issues, especially he observed and he is paying special attention to gender issues in her native Morocco. Much of his talk about the problems of sexuality in the dynamics of social life cannot be separated from Morocco Islam as a religious belief. It is universally thought of Fatima Mernissi actually wants to show partiality Islam on gender equality. Substantively Islam does not forbid women to politics, career, and obtain higher education. Fatima Mernissi further wants to show that Islam recognizes the rights, status, and role of women in almost all dimensions of life.